2005
DOI: 10.1007/s00280-005-0048-x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine-associated nonsteroidal anti-inflammatory drugs (NSAIDs) inhibit DNA synthesis and the growth of colon cancer cells in vitro

Abstract: The use of NSAIDs or COX-2 inhibitors for chemoprevention of colorectal cancer has been suggested for patients at high risk for this disease. However, the gastrointestinal side effects of traditional NSAIDs which consist of bleeding and ulceration, and the cardiovascular effects of COX-2 inhibitors may limit their usefulness. In preclinical studies, our laboratory has shown that the addition of phosphatidylcholine (PC) to the NSAIDs aspirin (ASA) or ibuprofen (IBU) results in a NSAID-PC with fewer GI side effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…This was consistent with a recent report which showed that NSAIDs could inhibit cell proliferation and promotes apoptosis [12] . Smith ML held a different view that aspirin could only inhibit the proliferation of sw480 colorectal cancer cells but not promote apoptosis [13] .…”
Section: Discussionsupporting
confidence: 92%
“…This was consistent with a recent report which showed that NSAIDs could inhibit cell proliferation and promotes apoptosis [12] . Smith ML held a different view that aspirin could only inhibit the proliferation of sw480 colorectal cancer cells but not promote apoptosis [13] .…”
Section: Discussionsupporting
confidence: 92%
“…The protective action of PC in this setting has been attributed to actions at the surface of gastric mucosal cells that is distinct from COX inhibition (35). However, there are indications that presentation of NSAID pre-associated with PC to cultured cells in vitro can increase the intracellular actions of the agents, including their COX-inhibitory activity (11,36). Whether this effect has any connection to the potentiation of COX inhibition by PC observed here is yet to be determined.…”
Section: In Vivo Implications Of Cox Inhibitor Potentiation By Pcmentioning
confidence: 61%
“…One example is that of Dial et al [51], who supplemented colon SW-480 with soy PC and nonsteroidal anti-inflammatory drugs, inhibiting the synthesis of 2-dymethilacetales (DMA) and limiting cell proliferation. Of note, C18:0 DMA are representative of plasmalogens, a type of PL abundant in membranes [52].…”
Section: Effects Of Pls On Cancermentioning
confidence: 98%